THE INFLUENCE OF SLOW DEEP BREATHING ON BLOOD PRESSURE OF HYPERTENSION PATIENT - Ni Putu Emy Darma Yanti (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Hypertension is one of non-communicable diseases, which is become major interest because mortality and morbidity of hypertension is the highest in the world. Slow deep breathing is non pharmacology therapy that can influence baroreflex and decrease the blood pressure. This research aimed to know the influence of slow deep breathing on blood pressure of hypertension patient in Puskesmas I Denpasar Timur. This research was pre experimental quantitative study. Design of this study was using one group pre test post test design with the intervention was slow deep breathing during 21 days, twice a day. The amount of sample in this study was 28 patients, in 35-80 years old which is chosen by simple random sampling technique. This research was conducted from  March 28th  until April 25th 2016. Univariate test was used to analyze respondent’s characteristics and bivariate test was used to analyze the difference of systolic and diastolic blood pressure to pre test and post test. The Bivariate test was using Wilcoxon because the data wasn’t  normal distributed. The result of bivariate test was significant (p-value =0,000), with level of confidence 5% so H0 was rejected. The conclusion of this study: there was influence of slow deep breathing in decrease the blood pressure of hypertension patients in Puskesmas I Denpasar Timur. Based on the result of this study, It is suggested to use slow deep breathing as non pharmacology therapy for hypertension. Key Word: Blood Pressure, Hypertension, Slow Deep Breathing